PECULIARITIES OF BREAST FEEDING OF PREMATURE CHILDREN - V.К. Kotlukov; L.G. Kuzmenko; N.V. Antipova; М.V. Polyakov ("Paediatrician" Publishers LLC, 2011)
The article presents main strategies of breast feeding of prematurely born infants support, such as use of Philips AVENT breast pumpfor lactation formation and feeding of the infant with native breast milk. Key words: premature infants, nursing mother, breast feeding support, modern accessories for breast feeding support. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (6): 170-175)